The International Handbook of the Demography of Race and Ethnicity
XXVI, 629 p. 97 illus.
Keywords: Examining key countries in every region of world, this handbook presents population profiles and analyses concerning racial/ethnic disparities and changing intergroup relations. Inside, prominent scholars from various parts of the world and disciplines address the links between stratification, demography, and conflict across the globe. Organized by region/continent, coverage for each profiled country includes demographic information; a historical overview that addresses past racial/ethnic conflict; identification of the most salient demographic trends and issues that the country faces; theoretical issues related to the linkages between stratification, demography, and conflict; methodological issues including quality of data and cutting-edge methods to better understand the issue at hand; and details on the possible future of the existing trends and issues with particular emphasis on public policy and human rights. This handbook will help readers to better understand the commonalities and differences that exist globally in the interplay between stratification, demography, and conflict. In addition, it also provides an excellent inventory of theoretical perspectives and methodological approaches that are needed to better comprehend this issue. This handbook will appeal to students, researchers, and policy analysts in the areas of race and ethnic relations, demography, inequality, international sociology, international relations, foreign studies, social geography, and social development.